Information System Web Based for Group Randomization of State Defense Education Class using Linear Congruential Method (Future Science, 2021)
One of the actual forms of state defense education is through outbound activities. In this context, education is interpreted as a process to humanize humans to become fully human adults. However, the world was shocked by the outbreak of a disease caused by a virus called corona or known as covid-19. Transmission through social contact between humans is difficult to predict and also cannot be avoided so its spread is also very rapid. Therefore, it is necessary to change the outbound state defense education method from conventional activities to offline activities based on the web and automatically computed. The system will replace the conventional process of supervising outbound activities where activities that are usually carried out in groups and simultaneously, will be carried out independently by sending evidence of activities that have been recorded through document files or videos. The results of this study are the Outbound State Defense Group Randomization Information System (SIOBEL) using the Linear Congruent Method (LCM) which helps in creating random groups of students and with the Graph Query Language (Graph-QL) system architecture which can facilitate interface and system developers to exchange data.